Physico-chemical and Microbiological Water Quality Assessment of Perisuyu River, Tunceli, Turkey - Kaplan, O.; Yildirim, N.C.; Yildirim, N.; Akyol, E.A. (Asian Journal of Chemistry, 2010)
Generally, the water quality depends on its chemical and microbiological conditions. So, in this study, the chemical and microbiological characteristics of the Perisuyu River through 4 year long surveillance in Tunceli, Turkey were studied. Sampling was carried out four times during the year. Nitrate, nitrite, ammonium concentrations, total dissolved solid, total coliform counts were determined and the presence of Escherichia coli, important water quality indicator, was tested. Generally in water samples E. coli and total coliform were found very high and nitrate, nitrite and ammonium concentrations were low. In 2008 August and 2009 February water pH was higher than the World Health Organization limit value. Electrical conductivity was higher in 2004 May, December and 2008 February.